Targeted antibiotic delivery using low temperature-sensitive liposomes and magnetic resonance-guided high-intensity focused ultrasound hyperthermia. (2nd April 2016) - Wardlow, Rachel; Bing, Chenchen; VanOsdol, Joshua; Maples, Danny; Ladouceur-Wodzak, Michelle; Harbeson, Michele; Nofiele, Joris; Staruch, Robert; Ramachandran, Akhilesh; Malayer, Jerry; Chopra, Rajiv; Ranjan, Ashish
Abstract: Chronic non-healing wound infections require long duration antibiotic therapy, and are associated with significant morbidity and health-care costs. Novel approaches for efficient, readily-translatable targeted and localised antimicrobial delivery are needed. The objectives of this study were to 1) develop low temperature-sensitive liposomes (LTSLs) containing an antimicrobial agent (ciprofloxacin) for induced release at mild hyperthermia (∼42 °C), 2) characterise in vitro ciprofloxacin release, and efficacy against Staphylococcus aureus plankton and biofilms, and 3) determine the feasibility of localised ciprofloxacin delivery in combination with MR-HIFU hyperthermia in a rat model. LTSLs were loaded actively with ciprofloxacin and their efficacy was determined using a disc diffusion method, MBEC biofilm device, and scanning electron microscopy (SEM). Ciprofloxacin release from LTSLs was assessed in a physiological buffer by fluorescence spectroscopy, and in vivo in a rat model using MR-HIFU. Results indicated that < 5% ciprofloxacin was released from the LTSL at body temperature (37 °C), while >95% was released at 42 °C. Precise hyperthermia exposures in the thigh of rats using MR-HIFU during intravenous (i.v.) administration of the LTSLs resulted in a four fold greater local concentration of ciprofloxacin compared to controls (free ciprofloxacin + MR-HIFU or LTSL alone). The biodistribution of ciprofloxacin in unheated tissues was fairly similar between treatment groups. Triggered release at 42 °C from LTSL achieved significantly greater S. aureus killing and induced membrane deformation and changes in biofilm matrix compared to free ciprofloxacin or LTSL at 37 °C. This technique has potential as a method to deliver high concentration antimicrobials to chronic wounds.